Volunteer tourism in the global south : giving back in neoliberal times - Vrasti, Wanda. (Interventions (Routledge (Firm)), 2013)
"This work explores the increasingly popular phenomenon of volunteer tourism in the Global South, paying particular attention to the governmental rationalities and socio-economic conditions that valorize it as a noble and necessary cultural practice"--